Homolysis/mesolysis of alkoxyamines activated by chemical oxidation and photochemical-triggered radical reactions at room temperature. Issue 23 (14th October 2021) - Audran, Gérard; Blyth, Mitchell T.; Coote, Michelle L.; Gescheidt, Georg; Hardy, Micael; Havot, Jeffrey; Holzritter, Maxence; Jacoutot, Samuel; Joly, Jean-Patrick; Marque, Sylvain R. A.; Koumba, Tataye Moussounda Moussounda; Neshchadin, Dmytro; et al.
Abstract : Instantaneous and spontaneous room temperature C–ON bond mesolysis of alkoxyamines triggered by chemical oxidation. Abstract : Alkoxyamines, which are connected with a phenol moiety by a (substituted) methylene bridge undergo homolytic cleavage upon chemical oxidation or a photo-induced hydrogen transfer. This selectively triggered reaction yields a nitroxide radical. In the presence of an excess of lead dioxide as the oxidant in tert -butylbenzene as solvent, spontaneous, instantaneous and almost quantitative generations of nitroxides from various alkoxyamines are observed at room temperature, which support activation energies for the cleavage lower than 100 kJ mol −1 . The rate and the amount of released nitroxide depend on the amount of "catalyst" and the structure of alkoxyamines.